Pharmacokinetic equivalence, comparable safety, and immunogenicity of an adalimumab biosimilar product (M923) to Humira in healthy subjects. Issue 1 (8th January 2018) - Hillson, Jan; Mant, Tim; Rosano, Molly; Huntenburg, Carolyn; Alai‐Safar, Mehrshid; Darne, Siddhesh; Palmer, Donna; Pavlova, Borislava G.; Doralt, Jennifer; Reeve, Russell; Goel, Niti; Weilert, Doris; et al.
Abstract: The aims of this randomized, double‐blind, three‐arm, single‐dose study were to demonstrate pharmacokinetic (PK) equivalence of the adalimumab biosimilar M923 (hereafter referred to as "M923") to each of 2 reference products, and to assess M923's safety and immunogenicity. Primary PK endpoints were maximum observed concentration ( C max ), area under the curve (AUC) from time 0 extrapolated to infinity (AUC0‐inf ), and AUC from time 0 to 336 hours (AUC0‐336 ). Secondary endpoints included safety and immunogenicity assessments. Healthy subjects were randomized 1:1:1 to receive a 40‐mg dose of M923 (n = 107); adalimumab US Humira (n = 105), hereafter referred to as "US Humira"; or adalimumab EU Humira (n = 103), hereafter referred to as "EU Humira." PK equivalence was demonstrated for all primary PK endpoints. Geometric least squares means ratios (GMRs) for C max, AUC0‐inf, and AUC0‐336 were 99.4, 100.9, and 100.5, respectively, between the M923 and EU Humira arms and 102.6, 104.2, and 102.9 between the M923 and US Humira arms. The 90% confidence intervals of the GMRs for all PK endpoints were within prespecified confidence bounds of 80%‐125%. Adverse event rates were similar across the M923 (47.7%), US Humira (50.9%), and EU Humira (53.3%) arms and were generally mild (73.7%) or moderate (22.0%). The proportion of subjects with a confirmed antidrug antibody (ADA) response was similar across study arms. This study demonstrated bioequivalent PK among M923, US Humira, and EU Humira and demonstrated that the PK parameters were consistent with similar safety and tolerability profile and ADA response rates.